Effect Strengthen of Reinforced Concrete Beams with Created Central Opening with CFRP around These Opening Under Combined Torsion and Bending - Ghandi Jahjah; Ihsan Altarsha; Dareen Alsalamah (Tishreen University, 2020)
The effect of torsion moments on reinforced concrete beams have much attention and complicate ,that if these moments are combined with shear and bending moments or act alone (pure torsion) . creating opening in these beams will reduce their strong a lot. This research study the effect of strengthening these beams , if we create opening in them , with CFRP to improve the ultimate torsion . The research conclude that creating an opening in the beams reduce the strength about 70% , while  strengthen with CFRP increase the strength about three times compared with beams with opening. يعد تأثير عزوم الفتل على الجوائز البيتونية المسلحة موضوع بغاية الأهمية والتعقيد , سواء أكانت عزوم الفتل هذه مترافقة مع الأفعال الإنشائية الأخرى من قص وعزوم انعطاف أو عزوم فتل صافية , وعند إحداث فتحة بهذه الجوائز تنقص مقاومتها بشكل كبير. تناقش الدراسة الحالية تأثير تقوية الجوائز البيتونية المسلحة الخاضعة لعزوم فتل وانعطاف، التي تحدث فيها فتحات أثناء الاستثمار وذلك باستخدام شرائح الألياف الكربونية CFRP . توصل البحث إلى عدة نتائج تؤكد أن إحداث الفتحات يؤدي إلى انخفاض المقاومة بنسبة تصل إلى 70% , بينما يزيد التدعيم بشرائح الألياف الكربونية المقاومة بنسبة كبيرة تصل إلى ثلاثة أضعاف مقاومته مع فتحات .